An analytical study of the principle of taking into account the direction of the wind during the establishment of marathon competitions in Iraq for the years (1980-2010) (Journal of the College of Basic Education, 2022)
Undoubtedly, scientific studies have contributed effectively to providing a lot of analyzes and useful information to the fields of sports training. The purposeful pursuit of achieving records for various sporting events, including the marathon event, requires the attention of those in charge of organizing the races of this event to the principle of wind direction when organizing this competition. The importance of the research lies in the fact that it works to achieve a competitive environment and conditions that are free from the most important natural obstacle that hinders the course of the marathon runner during the race, which is the wind blowing against the direction of the march.